Non-pharmacological treatment uptake for chronic musculoskeletal pain among community-dwelling older adults in Petaling district, Selangor - Lee, Foong Sim; Minhat, Halimatus Sakdiah; Ahmad, Siti Anom (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Chronic musculoskeletal pain is a common disabling condition among older adults with the majority, remain undertreated. This study aimed to determine the uptake of non-pharmacological treatment for chronic musculoskeletal pain among older adults and the associated factors. Methods: A stratified sampling proportionate to size with individual clinics as the strata were used to recruit 276 respondents from six public health clinics in Petaling district, one of the most aged districts in the state of Selangor, Malaysia. Based on the proportion calculated, eligible older adults were selected by systematic random sampling from the registration list. Data was collected using a pre-tested and validated questionnaire through a face-to-face interview with respondents. The questionnaire comprised of seven sections, namely, socio-demographic, comorbidity, depression, pain severity, treatment options, attitude towards chronic pain and chronic musculoskeletal pain. Inferential analysis was conducted using Chi-Square (X2) and Fisher’s Exact Tests. The P value of < 0.05 regarded as statistically significant. Results: A total of 242 (87.7%) of the respondents had chronic musculoskeletal pain, in which 235 (85.1%) were treated with non-pharmacological treatments. The commonly used non-pharmacological treatments were exercise (67.8%), biological-based therapies (40.9%) and massage (33.7%). The uptake of non-pharmacological treatment for chronic musculoskeletal pain among older adults was significantly associated with the presence of diabetes. Conclusion: The findings revealed the remarkably high uptake of non-pharmacological treatment among older adults who experienced chronic musculoskeletal pain which was significantly associated with diabetes and the presence of other diseases like high blood pressure, osteoarthritis, back pain and rheumatic arthritis.